2019
DOI: 10.1111/bcpt.13204
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of Rac1 in the bronchial smooth muscle of murine experimental asthma

Abstract: There has been considerable research on the involvement of RhoA/Rho kinase signalling in smooth muscle contractions. However, only a few reports have addressed the specific role of Rac1, which is a member of the Rho GTPase superfamily. Therefore, this study investigated the role of Rac1‐related pathways in bronchial smooth muscle (BSM) contractions. Bronchial rings isolated from mice were suspended in an organ bath, and the isometric contractions of circular smooth muscles were monitored. The phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The growth inhibition of BC cells induced by EHT1864 is related to the dual inhibition of PI3K-AKT-mTORC1 and MEK-ERK pathways (179). Studies have shown that Rac1 plays an important role in the contraction of various smooth muscles, such as bronchial smooth muscle, bladder smooth muscle, and prostate smooth muscle (180)(181)(182)(183). Although both EHT1864 and NSC23766 are Rac1 inhibitors, they have different pharmacological mechanisms in the inhibition of different smooth muscles (182,184,185), and EHT1864 tends to perform better (186,187).…”
Section: General Rac1 Inhibitormentioning
confidence: 99%
“…The growth inhibition of BC cells induced by EHT1864 is related to the dual inhibition of PI3K-AKT-mTORC1 and MEK-ERK pathways (179). Studies have shown that Rac1 plays an important role in the contraction of various smooth muscles, such as bronchial smooth muscle, bladder smooth muscle, and prostate smooth muscle (180)(181)(182)(183). Although both EHT1864 and NSC23766 are Rac1 inhibitors, they have different pharmacological mechanisms in the inhibition of different smooth muscles (182,184,185), and EHT1864 tends to perform better (186,187).…”
Section: General Rac1 Inhibitormentioning
confidence: 99%
“…2015; Kai et al . 2019 a , b ). Carbachol induced phosphorylation of both PAK T423 and β‐catenin S675 , but not β‐catenin S552 in C2C12 myotubes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2015; Kai et al . 2019 a , b ). This suggests the β‐catenin S675 phosphorylation may be sufficient to regulate glucose transport.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with those of our previous reports. 3,4) Recently, we have reported that Rac1 upregulation may be involved in augmented BSM contractions of Chal. mice.…”
Section: Resultsmentioning
confidence: 99%
“…2) Recently, we have demonstrated that Rac1 protein plays crucial role in G protein-coupled receptor (GPCR)-induced bronchial smooth muscle (BSM) contractions. 3) Further, we reported that Rac1 upregulation may be involved in augmented BSM contractions of repeatedly antigen-challenged (Chal.) mice.…”
Section: Introductionmentioning
confidence: 95%